2020
DOI: 10.1002/hec.4189
|View full text |Cite
|
Sign up to set email alerts
|

Information and sin goods: Experimental evidence on cigarettes

Abstract: We test the importance of information source on consumer choice in the context of sin goods, specifically electronic and tobacco cigarettes, among adult smokers. We proxy choice with intentions to vape and quit smoking in the next 30 days. We experimentally vary the information source: government, private companies, physicians, and no source. Our findings suggest that information source matters in the context of cigarettes choice for adult smokers. Private companies appear to be an important information source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 85 publications
(98 reference statements)
0
1
0
Order By: Relevance
“…Although the literature has shown that it is difficult to debias beliefs [27,28], there is evidence that perceptions of e-cigarettes change over time [29,30]. Changes in perceptions may be due to experiences [23][24][25], marketing [10], message framing [31] or federal or changes in state policy [32,33]. Policy changes and enforcement at the state and Federal levels to ban e-cigarettes in key flavors, tax e-cigarettes and ban sales to those under 21 years of age may indirectly aid in the debiasing of perceptions.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…Although the literature has shown that it is difficult to debias beliefs [27,28], there is evidence that perceptions of e-cigarettes change over time [29,30]. Changes in perceptions may be due to experiences [23][24][25], marketing [10], message framing [31] or federal or changes in state policy [32,33]. Policy changes and enforcement at the state and Federal levels to ban e-cigarettes in key flavors, tax e-cigarettes and ban sales to those under 21 years of age may indirectly aid in the debiasing of perceptions.…”
Section: Policy Implicationsmentioning
confidence: 99%